Acute Myocardial Infarction due to External Compression of the Left Main Coronary Artery by a Large Pulmonary Artery Aneurysm. (23rd February 2021) - Sharma, H.; Doshi, S. N.; Nadir, M. A.
Abstract : Background . Although rare, external compression of the left main coronary artery (LMCA) by a pulmonary arterial aneurysm (PAA) as a consequence of pulmonary arterial hypertension causing stable angina pectoris is well described. However, acute myocardial infarction is extremely rare, particularly with a full array of electrocardiographic, biochemical, and echocardiographic features, as in this scenario. Case. In this case, a 62-year-old man with a past history of severe fibrotic lung disease was hospitalised with chest pain. The patient had dynamic anterolateral ischaemic changes on electrocardiography and serially elevated high-sensitivity troponin I. Transthoracic echocardiography revealed impaired left ventricular ejection fraction with anterolateral hypokinesis. Coronary angiography with intracoronary imaging revealed external compression of the LMCA. Computer tomography (CT) scans confirmed new PAA, compared to previous scans. The patient was successfully treated by percutaneous coronary stent implantation. Conclusion. Progressive dilatation of the pulmonary artery due to pulmonary arterial hypertension can result in acute MI secondary to external compression of the LMCA. Clinicians should be mindful of acute coronary syndromes in patients with long-standing pulmonary hypertension presenting with chest pain.